Enhancing inferential abilities in adolescence: new hope for students in poverty - Gamino, Jacquelyn F.; Motes, Michael M.; Riddle, Russell; Lyon, G. Reid; Spence, Jeffrey S.; Chapman, Sandra B. (Frontiers in Human Neuroscience, 2014)
The ability to extrapolate essential gist through the analysis and synthesis of information, prediction of potential outcomes, abstraction of ideas, and integration of relationships with world knowledge is critical for higher-order learning. The present study investigated the efficacy of cognitive training to elicit improvements in gist-reasoning and fact recall ability in 556 public middle-school students (grades seven and eight), versus a sample of 357 middle school students who served as a comparison group, to determine if changes in gist-reasoning and fact recall were demonstrated without cognitive training. The results showed that, in general, cognitive training increased gist-reasoning and fact recall abilities in students from families in poverty as well as students from families living above poverty. However, the magnitude of gains in gist-reasoning varied as a function of gender and grade-level. Our primary findings were that seventh and eighth grade girls and eighth grade boys showed significant increases in gist-reasoning after training regardless of socioeconomic status. There were no significant increases in gist-reasoning or fact recall ability for the 357 middle school students who served in the comparison group. We postulate that cognitive training in middle school is efficacious for improving gist-reasoning ability and fact recall in students from all socioeconomic levels.